2022
DOI: 10.3390/healthcare10112215
|View full text |Cite
|
Sign up to set email alerts
|

Relative Handgrip Strength Mediates the Relationship between Hemoglobin and Health-Related Quality of Life in Older Korean Adults

Abstract: Background: Little is known regarding how anemia and handgrip strength influence the health-related quality of life (HRQoL) of older populations. This population-based study aimed to examine whether handgrip strength mediates the association between anemia and HRQoL in a representative sample of 6892 Korean adults aged ≥ 65 years (3753 females). Methods: HRQoL was assessed with the EuroQol-5 dimension. Anemia was defined according to World Health Organization (WHO) criteria, and handgrip strength was measured … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…Kim et al . [ 28 ] also found that people with weak HGS had a higher probability of having a lower QOL (OR = 1.429, P < 0.001). According to Xie and Ma (2021), maintaining or developing grip strength is vital in delaying or reducing QOL among the community-dwelling elderly.…”
Section: Discussionmentioning
confidence: 95%
“…Kim et al . [ 28 ] also found that people with weak HGS had a higher probability of having a lower QOL (OR = 1.429, P < 0.001). According to Xie and Ma (2021), maintaining or developing grip strength is vital in delaying or reducing QOL among the community-dwelling elderly.…”
Section: Discussionmentioning
confidence: 95%